Determination of potentially toxic elements in selected vegetables sampled from some markets in the Kumasi metropolis. Issue 1 (31st December 2022) - Apau, Joseph; Siameh, Margaret Ohui; Misszento, Jemima Adwoa; Gyamfi, Opoku; Osei-Owusu, Jonathan; Kwaansa-Ansah, Edward Ebow; Acheampong, Akwasi
Abstract: Lead, cadmium, arsenic, and copper are potentially toxic elements that are of concern to man because of their negative effects on human health. The Atomic Absorption Spectrometer was used to evaluate the quantities of these heavy metals, and a value of heavy metal consumption in human meals was derived to determine the danger to human health. The mean cadmium content in the three vegetables from the four market sites varied from 0.60 mg/kg to 1.33 mg/kg, above the Food and Agricultural Organization/World Health Organization permissible limit. Lead, arsenic, and copper had mean values ranging from 0.064 mg/kg to 0.106 mg/kg, 0.003 mg/kg to 0.004 mg/kg, and 12.35 mg/kg to 21.54 mg/kg, respectively, all of which were below the World Health Organization's maximum limit for each heavy metal. The Target Hazard Quotient (THQ) was used to determine the health risk that these heavy metals posed to vegetable eaters. Cadmium and copper THQ levels were greater than the acceptable limit of 1 in both adults and children, whereas lead THQ values were higher in just children, indicating a considerable health risk to the population. Arsenic THQ levels in both populations and lead THQ values in the adult population were both below the acceptable limit of 1, indicating that there was no major health risk to the population.